Environmental impact assessment of different strategies for the remanufacturing of user electronics - Mann, Angad; Saxena, Prateek; Almanei, Mohammed; Okorie, Okechukwu; Salonitis, Konstantinos (MDPI, 2022)
Over the years, the innovation and development of electrical and electronic equipment have been on a steep rise. Millions of electronics are being sold or discarded every year in the form of waste. Sustainable IT (Green IT or Circular Computing) is one of the most environment-friendly methods of reusing discarded or waste user electronics. The remanufacturing of a computer refers to the disassembly, repair, and upgrade of the original computer to give it a new life, along with a warranty that is as good as a new product. The goal of this work includes studying and assessing the total environmental impact of refurbishing a computer using life cycle assessment (LCA) integrated with discrete event simulation (DES), to compare two business models: (1) a case of centralized remanufacturing where the plants are in the Middle East, which is the hub for receiving waste electronics and distributing remanufactured goods; (2) a case of decentralized remanufacturing where the plants are situated in each continent for over a range of computer models. The environmental assessment was conducted using the openLCA software in combination with the WITNESS Horizon software for the DES. The results show that decentralized remanufacturing is a much more environmentally friendly option for the remanufacturing of computers, and the decentralized remanufacturing operation has a better throughput as well as efficiency, as compared to the centralized remanufacturing operation. The centralized remanufacturing scenario has a climate change impact of 1035.19 kg of CO2-Eq, as compared to the decentralized remanufacturing scenario with an impact of 816.12 kg of CO2-Eq. In terms of the impact on the marine life, decentralized remanufacturing was found to have 0.28 kg of N-Eq impact, as compared to centralized remanufacturing (0.22 kg of N-Eq). However, this does not give us a complete picture, as the environmental impact of the computer in its previous life remains unknown. Multi life cycle assessment is the assessment process that can be used to get a clearer picture of the ecological footprint of the computer during its multiple life cycles.
Keywords: sustainability; life cycle assessment; discrete event simulation; supply chain; remanufacturing